Social Return on Investment of an Innovative Employment Option for Persons with Developmental Disabilities: Common Ground Co‐operative. Issue 2 (5th November 2015) - Owen, Frances; Li, Jingyu; Whittingham, Lisa; Hope, Jennifer; Bishop, Courtney; Readhead, Anne; Mook, Laurie
Abstract : Common Ground Co‐operative (CGC) provides training, administrative, and job coach support to five social enterprises for which persons with developmental disabilities are the non‐share‐capital partners. This study examines the use of social return on investment (SROI) as a means of determining the value of program impacts related to quality‐of‐life changes for enterprise partners and their families. The process of conducting this SROI analysis is described and analyzed in terms of its utility in employment services for persons with developmental disabilities.